2020
DOI: 10.1097/cce.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Neurological Blood-Based Biomarkers in Critically Ill Patients With Coronavirus Disease 2019

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 27 publications
3
53
2
Order By: Relevance
“…We concluded that changes in these CNS damage biomarkers were more pronounced in hospitalized patients compared to non-hospitalized individuals and healthy controls [8] . Results confirming this have subsequently been reported in other studies [ 9 , 10 ]. In addition, in the search for useful biomarkers to predict COVID-19 outcomes, cytokine growth differentiation factor 15 (GDF-15) was recently proposed as a biomarker of general disease severity and unfavourable outcomes [11] .…”
Section: Introductionsupporting
confidence: 92%
“…We concluded that changes in these CNS damage biomarkers were more pronounced in hospitalized patients compared to non-hospitalized individuals and healthy controls [8] . Results confirming this have subsequently been reported in other studies [ 9 , 10 ]. In addition, in the search for useful biomarkers to predict COVID-19 outcomes, cytokine growth differentiation factor 15 (GDF-15) was recently proposed as a biomarker of general disease severity and unfavourable outcomes [11] .…”
Section: Introductionsupporting
confidence: 92%
“…In a relatively small study including as controls ICU patients with pneumonia of other etiology, patients with COVID-19 were found to have significantly higher blood GFAP levels. Furthermore, GFAP, UCH-L1, and NfL positively correlated with Intensive Care Delirium Screening Checklist score and were increased in patients with delirium in the COVID-19 group but not in the ICU controls [ 24 ]. In another study, NfL and GFP blood levels measured at hospitalization were found to be more elevated in patients with fatal outcome [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small study investigating a large number of biomarkers, has found elevated total tau levels in blood extracellular vesicles in COVID-19 patients as compared to historical controls [ 26 ]. Finally, no associations were found between NfL, GFAP, UCH-L1 or tau and respiratory function or cytokines in COVID-19 patients [ 24 ]. The measures in all these studies were performed in samples not obtained early at hospital admission, but rather during disease course or even in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral axonal injury can potentially contribute to increased plasma concentrations of NfL and GFAp, a strong correlation between plasma and CSF concentration was seen in patients with neurological symptoms, suggesting that plasma levels parallel CSF levels in patients with neuro‐COVID (Virhammar, Naas, et al., 2020). In critically ill patients treated in the ICU, significantly higher plasma GFAp was seen in patients with COVID‐19 than in patients with respiratory failure due to other causes (Cooper et al., 2020). Higher plasma NfL was also seen in patients with delirium.…”
Section: Csf and Serum Biomarkers Of Cns Involvement In Covid‐19mentioning
confidence: 99%
“…Higher plasma NfL was also seen in patients with delirium. However, patients with COVID‐19 were older than controls and the number of patients were small, making the evaluation of results uncertain (Cooper et al., 2020). Higher serum NfL was also seen in 29 COVID‐19 ICU patients compared to 10 general ICU patients after adjusting for neurological comorbidities and age (Sutter et al., 2020) Although these studies are limited in size, results may indicate that additional neuronal damage can potentially be associated with COVID‐19 beyond what is seen a non‐COVID‐19 ICU population.…”
Section: Csf and Serum Biomarkers Of Cns Involvement In Covid‐19mentioning
confidence: 99%